LITERASI DAN NUMERASI PEMBELAJARAN MATEMATIKA BERBASIS MASALAH UNTUK MENGEMBANGKAN KEMAMPUAN BERFIKIR KRITIS DAN KREATIF SISWA - Sulasih Sulasih; Mufidatik Mufidatik; Nur Fauziyah (SIGMA, 2022)
The purpose of this research is to strengthen the literacy and numeracy of students in problem-based learning so that they can develop their ability to think critically and creatively. Based on the experience of the writer who teaches at SMP N 1 Gresik class VIII D the ability of students to read and understand implied information and interpret meaning in mathematical problems both in writing and in infographics (literacy) is still lacking, this also results in mathematical abilities related to identify what is known, what is asked, formulate, use concepts, procedures, and mathematical tools (Numerations) which are used to solve problems are also low which results in low critical and creative thinking skills in solving mathematical problems. To overcome these problems, the researchers tried to strengthen Literacy and Numeracy in Problem-Based Learning to Develop Critical and Creative Thinking Skills for Class VIIID SMPN 1 Gresik on the Topic System of Two Variable Linear Equations (SPLDV). This study uses a descriptive method with a qualitative approach. The results of this study indicate an increase in the critical and creative thinking skills of Class VIIID SMPN 1 Gresik students on the SPLDV topic as measured by using critical and creative thinking indicators